2020
DOI: 10.1111/and.13784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol on the changes in testicular protein expression in adult male rats

Abstract: It is well known that ethanol consumption is the cause of liver disease (Kawaratani et al., 2013), gastric and colon cancers (Na & Lee, 2017), and renal dysfunctions (Kumar & Vasudevan, 2008). In addition, ethanol has a detrimental effect on sexual behaviour and fertility (Ávila et al., 2016; Gude, 2012). Previous studies showed that ethanol consumption could affect male reproductive system in adult male rats (Nishi et al., 2018; Yari, Karamian, Asadbegy, Hoseini, & Moazzami Farida, 2018). Previous study showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…Besides the alterations in the semen quality (lower sperm concentration, motility, and percentage of normal forms), Rahimipour et al also reported reduced DNA condensation and integrity in mice fed with ethanol compared to controls, along with increased apoptotic rates [ 85 ]. In addition, in vitro experiments showed an accelerated acrosomal loss occurring during the sperm capacitation of human and animal sperm incubated in ethanol, further reducing their fertilizing ability [ 124 , 125 , 126 , 127 ]. This is probably due to the capacity of ethanol to alter lipid fluidity and membrane permeability through the oxidation of the membranes’ lipids and proteins [ 127 ].…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 99%
“…Besides the alterations in the semen quality (lower sperm concentration, motility, and percentage of normal forms), Rahimipour et al also reported reduced DNA condensation and integrity in mice fed with ethanol compared to controls, along with increased apoptotic rates [ 85 ]. In addition, in vitro experiments showed an accelerated acrosomal loss occurring during the sperm capacitation of human and animal sperm incubated in ethanol, further reducing their fertilizing ability [ 124 , 125 , 126 , 127 ]. This is probably due to the capacity of ethanol to alter lipid fluidity and membrane permeability through the oxidation of the membranes’ lipids and proteins [ 127 ].…”
Section: Alcohol Consumption and Male Infertility: Evidence From Animal And Human Studiesmentioning
confidence: 99%
“…However, the microenvironment interaction between epididymal AKAP4 and spermatozoa should be further investigated. Moreover, testicular and sperm TyrPho protein expressions in CUMS mice were decreased, relating to other infertile conditions demonstrated in animal models (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al., 2016; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al., 2016; Burawat et al., 2018; Iamsaard et al., 2014; Sampannang et al., 2019; Sukhorum & Iamsaard, 2017; Tangsrisakda & Iamsaard, 2020; Tongpan et al., 2019). Although TyrPho proteins have been localised in the testis, seminal vesicle and epididymal spermatozoa (Chaichun et al., 2017; Sati et al., 2014; Tongpan et al., 2019), the functional associations between such proteins and AKAP4 are still unknown.…”
Section: Discussionmentioning
confidence: 87%
“…Particularly, the TyrPho proteins like AMP‐activated protein kinases (AMPKs) are essential for capacitation and acrosome reaction in mammalian spermatozoa (Ickowicz et al., 2012; Zhu et al., 2018). Moreover, alterations of TyrPho proteins expression in testis and reproductive tracts have been demonstrated in subfertile animal models including diabetes (Sampannang et al., 2019; Yannasithinon & Iamsaard, 2019), drug treatments (Burawat et al., 2018; Iamsaard et al., 2014; Sukhorum & Iamsaard, 2017; Tongpan et al., 2019), stress (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al., 2016; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al., 2016) and alcohol consumption (Tangsrisakda & Iamsaard, 2020). To provide additional knowledge about infertility caused by stress, this study aimed to reveal the effect of CUMS on sexual behaviour, sperm quality, and expressions of AKAP4 and TyrPho proteins in testis, epididymis, and spermatozoa of adult mice.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has localised the TyrPho in the cytoplasm of principle cells, nuclei of apical and basal cells, and fluid of rat caudal epididymis (Sawatpanich et al., 2018). Although the actual functions of TyrPho proteins in epididymal fluid need to be further elucidated, previous studies have shown the alteration of TyrPho protein expressions in several subfertile models including stress (Arun et al., 2016; Iamsaard et al., 2020; Tangsrisakda & Iamsaard, 2020; Sampannang et al., 2019; Sukhorum & Iamsaard, 2017; Tongpan et al., 2019; Yannasithinon & Iamsaard, 2019; Yannasithinon & Iamsaard, 2020). Under CS investigated in this study, the TyrPho protein expressions of epididymal fluids and head epididymal tissue were mostly shown for the first time to be decreased but increased in the tail epididymal tissue.…”
Section: Discussionmentioning
confidence: 99%